PENGARUH PROFITABILITAS, LIKUIDITAS DAN LEVERAGE TERHADAP NILAI PERUSAHAAN - Ida Yusnita (Gapenas Publisher, 2021)
This study aims to determine the effect of profitability, liquidity and leverage on firm value of PT. HM Sampoerna Tbk. For the period 2011-2020, partially and simultaneously, this study explains the factors that affect Firm Value. These factors are Profitability, Liquidity and Leverage. The data used in this study is secondary data, namely Summary of Financial Statement data obtained from the financial statements of PT. HM Sampoerna Tbk. Listed on the Indonesia Stock Exchange for the period 2011-2020. Based on the results of data analysis that has been carried out on all data obtained, it can be concluded as follows:1) Profitability using (ROE) has a partial and insignificant effect on firm value as evidenced by the value of sig = 0.285 > 0.05 and -tcount > -ttable (-1.172 > -2.447) so that the hypothesis I acceptable.2) Liquidity using (CR) does not have a partial and significant effect on firm value as evidenced by the value of sig = 0.956 > 0.05 and tcount ttable (0.057 < 2.447) so that hypothesis II cannot be accepted. 3) Leverage using (DER) has no partial and insignificant effect on firm value as evidenced by the value of sig = 0.964 <0.05 and tcount ttable (0.048 < 2,447) so that the third hypothesis is not accepted. 4) Profitability, Liquidity and Leverage have no simultaneous effect on Firm Value, as evidenced by the value of sig = 0.287 > 0.05 and fcount ftable (1.59 ? 4.76) so that hypothesis IV cannot be accepted